Obstacle Detection And Avoidance System - Yew, Chang Chern (Universiti Sains Malaysia, 2018)
Current technology trend is moving towards automation and people need things to be done automatically. The obstacle detection and avoidance system is being researched to study its application in automated machine. Few electronic components like sensors and robot car as experiment tool are needed to study this system and the motion or kinematics of the system is also studied throughout the research. The application of this system is mostly for moving vehicle in indoor. In order to make this system works, the effect of obstacle material in the environment to the response of the sensing unit is studied and few experiments are carried out to ensure better performance in the system. The determination of the threshold distance to be set in the sensors will get the system to work better in obstacle avoiding. The algorithm on how the robot car responses when obstacle is detected is also designed. The algorithm sets to interpret the data obtained from the sensor and makes the decision for the mobile robot to react. The robot car is designed to avoid obstacle detected in front of the robot car and continues to move back the path in straight line. The robot car makes its own decision using Fuzzy Logic method to avoid obstacle with the condition set. The robot car able to move and avoid obstacle in less than thirty seconds of response time with experiment conducted as prove.